2021
DOI: 10.3390/cancers13225808
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Preservation Treatments in Sarcomas: Oncological Problems and Reproductive Results: A Systematic Review

Abstract: Uterine sarcomas are rare cancers, sometimes diagnosed in women of childbearing age. Hysterectomy is the standard treatment in early stages. The option of lesion removal to save fertility is described in the literature, but it is still considered experimental. The objective of this systematic review is to report on the available evidence on the reproductive and oncological outcomes of fertility-sparing treatment in women with uterine sarcomas. PubMed, Scopus and Cochrane Central Register of Controlled Trials w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The treatment of choice is surgical, performing total abdominal hysterectomy or by laparoscopic approach, with or without bilateral salpingo-oophorectomy; in women of reproductive age, a myomectomy and polypectomy may be chosen. There is no standardized chemotherapy, hormonal therapy, or radiation therapy in UA, due to the small number of patients with this neoplasia; however, standardized chemotherapy for uterine sarcomas, such as doxorubicin, ifosfamide, or gemcitabine/docetaxel, and newer drugs, such as trabectedin, appear to have some efficacy in UASO ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of choice is surgical, performing total abdominal hysterectomy or by laparoscopic approach, with or without bilateral salpingo-oophorectomy; in women of reproductive age, a myomectomy and polypectomy may be chosen. There is no standardized chemotherapy, hormonal therapy, or radiation therapy in UA, due to the small number of patients with this neoplasia; however, standardized chemotherapy for uterine sarcomas, such as doxorubicin, ifosfamide, or gemcitabine/docetaxel, and newer drugs, such as trabectedin, appear to have some efficacy in UASO ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, three (27.27%) patients conceived and a total of five children were born. The most recent systematic review regarding uterine preservation treatment in sarcomas was published by Dondi et al (2021) [ 39 ]. The authors reported to have found 37 eligible papers, of which only four were case series, like our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a large cohort of 153 LG-ESS, 19 patients underwent myomectomy with ovary-sparing procedures to preserve fertility, and 4 (21%) developed recurrence ( 8 ). Recently, a systematic review focused on fertility-sparing surgery for uterine sarcomas reported a recurrence risk of 54%, however, this result was based on 5 very heterogeneous studies with a relatively low number of patients ( 18 ).…”
Section: Discussionmentioning
confidence: 99%